Performance differences between winning and losing under-19, under-21 and senior teams in men`s beach volleyball - Medeiros, A. I. A.; Marcelino, R.; Mesquita, I. M.; Palao, J. M. (International Journal of Performance Analysis in Sport, 2017)
This study aimed to compare beach volleyball performance indicators between winning and losing teams in different age groups. Game actions from the 2010 to 2011 Men`s World Championships were observed using video match analysis (6095 from under-19, 5138 from under-21 and 8705 from senior matches). Variables assessed were: number of points won in each complex of the game, number of points and errors by game action (serve, attack in side-out, attack in counterattack, block and other errors); and performance coefficient of game actions (serve, reception, set in side-out, set in counterattack, attack in side-out, attack in counterattack, block and dig). Practical significance of data was analysed using magnitude-based inferences. Results have showed similar patterns in the three age groups. There were differences in the game profile according to the game result and age group. Winning teams scored more points in counterattack: points from the opponent`s attack errors, counterattack points, block points and points from other errors. The article provides new insights to beach volleyball coaches and performance analysts, emphasising the need to consider the interaction between different performance indicators, both in training process and match analysis in beach volleyball.